Kaupapa Māori Methodology: Trusting the Methodology Through Thick and Thin - Hiha, Anne Aroha (The Australian Journal of Indigenous Education, 2015)
Kaupapa Māori is thoroughly theorised in academia in Aotearoa and those wishing to use it as their research methodology can find support through the writing of a number of Māori academics. What is not so well articulated, is the experiential voice of those who have used Kaupapa Māori as research methodology. My identity as a Māori woman researching with Māori women became integral to my methodology and approach to the research. The highs and lows of my research experiences with Kaupapa Māori methodology are examined in this article. The discussion contends that Kaupapa Māori research methodology can be a framework, guide and support for research within a Māori context and adds an experiential aspect to understanding the wider field of Indigenous research methodology. My hope is that through my experience with Kaupapa Māori methodology other Māori and Indigenous researchers will be eager to embrace their own research methodologies.